The Study of Ten Poems Written by William Blake - Reza, Reza Rezita; Ira Maisarah (Journal of English for Specific Purposes in Indonesia, 2024)
This study aims to present findings focused on the analysis of figurative language and central themes in a collection of ten poems by William Blake. Qualitative research methodology is used to conduct a comprehensive analysis. Among the ten poems, the writer discovered that the predominant use of figurative language is metaphors. Furthermore, the theme explored in the poem "Ah Sunflower" pertains to the concept of life beyond death, and the theme depicted in "The Sick Rose" revolves around desire and passion, then the theme conveyed in "A Poison Tree" revolves around anger and negative emotions. In contrast, the theme depicted in "A Dream" revolves around the narrative of an individual's life. The theme explored in "A Divine Image" pertains to the portrayal of humanity. "The Tyger" revolves around religious beliefs, portraying God as powerful and magnificent. "Infant Joy" revolves around the dialogue between a child and an adult. The central idea explored in "London" revolves around portraying the daily experiences of individuals residing in London. The poem explicitly highlights Blake's dissatisfaction with the prevailing political circumstances during his existence. The central theme of "Love Secret" revolves around emotions, feelings, and the power of imagination. The primary theme of the final poem, "The Lamb," delves into matters of spirituality, mainly focusing on the grandeur of God, His creations, the presence of peace, and the quality of gentleness. The predominant theme frequently explored by the writer centered around the relationship between humanity and the divine.